The Effect of Dexmedetomidine on Lumbar Epidural Injection for Failed Back Surgery Syndrome - Ashraf Eskandr; Sadik Abdel Maseeh (Anesthesiology Research and Practice)
Purpose. Failed back surgery syndrome is a chronic pain condition requiring rapid, effective, and efficient management. This study evaluates the effect of adding dexmedetomidine to lumbar epidural steroids in patients with failed back surgery syndrome. Methods. Fifty patients suffering from failed back surgery syndrome were randomly assigned to one of two groups, receiving an epidural injection of 20 mL of either a mixture of betamethasone (14 mg) and bupivacaine 0.5 mg (group C) or a mixture of betamethasone (14 mg), bupivacaine 0.5 mg, and dexmedetomidine (0.5 μg/kg) (group D) adjusted to the volume with normal saline. The effect was evaluated using visual analogue scale (VAS), analgesic requirement, and Oswestry disability index 2 weeks, 4 weeks, 8 weeks, and 12 weeks after injection. Results. VAS and ibuprofen consumption showed a significant reduction in group D. The Oswestry disability index was significantly improved in group D. There were no records of hypotension, bradycardia, sedation, or hypoxemia in both groups. Conclusion. The present study demonstrated potential safe and effective usage of adding dexmedetomidine to epidural steroid to control pain in patients with failed back surgery syndrome.